Recovery of Sphagnum mosses in donor sites after cutting: effects of species and some environmental factors - Edgar Karofeld; Kai Vellak; Arvo Tullus (Mires and Peat)
Spontaneous revegetation of extracted peatlands is a very slow and sporadic process and, therefore, Sphagnum fragments cut from donor sites are often used for restoration. In two bogs in central and north-east Estonia, we studied the recovery and growth of Sphagnum fuscum, Sphagnum rubellum and Sphagnum medium after cutting of donor sites, in comparison with natural bog sites. On average, the water table was 13.8–17.4 cm higher in spring than in autumn, in both natural and donor sites, and mostly higher in the latter by 1.2–8.1 cm. Shoot length increment, density and weight of capitula of Sphagnum mosses were lower in the donor sites than in natural bog sites. The cover of Sphagnum mosses reached 5–50 % over a period of 3–11 years after cutting, indicating much slower recovery than has been reported previously. Of the Sphagnum species studied, S. fuscum showed better recovery in the donor sites. As the weather was similar in the natural and donor sites and the water table was mostly higher in the donor sites, the growth of Sphagnum mosses is most probably impeded by the combination of interrupted capillary water rise and a more pronounced drought effect in the donor sites. To promote revegetation of donor sites, plant fragments should be cut from the uppermost <10 cm only, and not from the entire area but instead leaving uncut patches or stripes to enable faster spreading of plants. Because of the slow recovery of donor sites, cutting of Sphagnum fragments from natural bogs should be avoided, and sites bordering expanding peat extraction areas should be chosen in preference.